EKSPLORASI GULA SIWALAN PADA PEMBUATAN SIRUP JAMU ANAK MELALUI PEMBERDAYAAN PEREMPUAN DESA LEMBUNG TIMUR KABUPATEN SUMENEP - Nurul Inayah; Enni Mutiati; Mohammad Nurul Hidayatullah (Universitas Mataram, 2026)
Lembung Timur Village is an area surrounded by siwalan trees, which are known for their brown sugar production. Brown sugar is a natural sweetener with a low glycemic index. Therefore, it is suitable for use as an ingredient in food and beverages as a substitute for cane sugar. Jamu herbal medicine tends to be unpopular with children due to its distinctive taste and smell. Therefore, it is necessary to explore the use of palm sugar in making herbal medicine for children to reduce the bitter taste. This community service activity involved 23 participants, namely mothers from the Lembung Timur Village PKK. The purpose of implementing Community Service (PKM) is to improve the quality and quantity of low-calorie palm sugar processing as an ingredient in herbal medicine that meets standardized quality standards. The implementation method consisted of preparation, counseling, training in making herbal syrup for children with the addition of palm sugar, TTG provision, and evaluation. The results of this community partnership program were 1) an increase in the partners' knowledge in making palm sugar herbal syrup. The enthusiasm of the participants was reflected in their active participation in asking questions and expressing their opinions. The evaluation showed a 50%-80% increase in knowledge compared to before the PKM activity. In addition, the tabulation of data on the partners' satisfaction with all PKM activities was above 50%. 2) An increase in the quantity of products produced, namely with the provision of TTG, which was able to produce 8-15 liters per cycle, or the equivalent of 32-60 bottles of ready-to-consume syrup. Through this program, it is hoped that the welfare of the community will improve through health and economic independence and that it will contribute to the progress of the village.